The Stravinsky legacy - Cross, Jonathan 1961- (Cambridge Cambridge University Press, 1998)
It has become increasingly apparent in recent decades that Stravinskys music has had far-reaching influence on the development of music in our century. Stravinskys modernist innovations - evident in such features as his musics discontinuity, its stasis, its ritualized anti-narrative, its novel rhythmic and formal structures, its articulation of new kinds of musical time, and its reinterpretation of music and materials from the past - have helped shape much of the music of our time. This book represents a first substantial attempt to evaluate Stravinskys technical and aesthetic legacy. In Part I (The Stravinsky Legacy), Jonathan Cross explores the breadth of Stravinskys impact on the music of composers as diverse as Adams, Andriessen, Birtwistle, Boulez, Carter, Messiaen, Reich, Stockhausen, Tippett, Varèse and Xenakis. In Part II (Stravinsky Reheard) he returns to Stravinskys neoclassical music to examine how recent developments in composition and musicology affect our understanding of and analytical approaches to Stravinsky.
Keywords: Stravinsky, Igor -- 1882-1971; 20th Century (1901-2000); Composer; Legacy; Russia; Paris (France); Venice (Italy); USA